Investigating a Virtual Reality-based Emergency Response Scenario and Intelligent User Interface for First Responders. (December 2020) - Spain, Randall; Saville, Jason; Lui, Barry; Slack, Donia; Hill, Edward; Holloway, John; Norswothy, Sarah; Mott, Bradford; Lester, James
Because advances in broadband capabilities will soon allow first responders to access and use many forms of data when responding to emergencies, it is becoming critically important to design heads-up displays to present first responders with information in a manner that does not induce extraneous mental workload or cause undue interaction errors. Virtual reality offers a unique medium for envisioning and testing user interface concepts in a realistic and controlled environment. In this paper, we describe a virtual reality-based emergency response scenario that was designed to support user experience research for evaluating the efficacy of intelligent user interfaces for firefighters. We describe the results of a usability test that captured firefighters' feedback and reactions to the VR scenario and the prototype intelligent user interface that presented them with task critical information through the VR headset. The paper concludes with lessons learned from our development process and a discussion of plans for future research.